2010
DOI: 10.3109/08860220903375286
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Skin Microcirculation during Hemodialysis

Abstract: Background. Cardiovascular mortality in hemodialysis (HD) patients remains high despite improvements in HD technique such as dialysis adequacy, dialysis fluid purity, and membrane biocompatibility. Optimal fluid balance to maintain optimal hemodynamic stability during hemodialysis (HD) procedure is essential. At the present time, hemodynamic stability is conventionally assessed as stability of macrocirculation, especially as maintenance of systemic blood pressure with no attention paid to peripheral perfusion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This supports earlier studies which had proposed that there are a number of changes to the circulation described as the DeJager‐Krogh phenomenon 29 . In this phenomenon, there is a reduction in blood flow to the skin, with pooling of blood in the large elastic capacitance veins, including the portal venous system when starting dialysis 30–32 . This effect may have been amplified as dialysis was performed with patients lying supine on beds.…”
Section: Discussionsupporting
confidence: 84%
“…This supports earlier studies which had proposed that there are a number of changes to the circulation described as the DeJager‐Krogh phenomenon 29 . In this phenomenon, there is a reduction in blood flow to the skin, with pooling of blood in the large elastic capacitance veins, including the portal venous system when starting dialysis 30–32 . This effect may have been amplified as dialysis was performed with patients lying supine on beds.…”
Section: Discussionsupporting
confidence: 84%
“…In the literature, the majority of studies that have investigated the impact of HD on the smallest vessels have referred to microcirculation in the skin. 17,[22][23][24] Most of these data indicate that the microcirculation in the skin deteriorates during the HD procedure 17,[22][23][24] and patients with diabetes and peripheral arterial occlusive disease are more susceptible to impairments in the peripheral microcirculation and are at high risk of gangrene. [23][24][25] Changes in the skeletal muscle microcirculation during a HD session have been recorded by De Βlasi et al 4 using a NIRS device (NIMO-4 tissue probe; Nirox Srl, Brescia, Italy).…”
Section: Discussionmentioning
confidence: 99%
“…Mistrik et al have recently demonstrated microcirculatory changes during HD by using laser Doppler methods [18]. Previously, Weiss et al published results on the decrease in the TCPO2 measurement during hemodialysis and up to four hours after the end of the session [19].…”
Section: Discussionmentioning
confidence: 99%